Resource loss, religiousness, health, and posttraumatic growth following Hurricane Katrina - Cook, Stephen W. (Mental health, religion & culture, 2013)
This study examined associations among resource loss, religiousness (including general religiousness, religious comfort, and religious strain), posttraumatic growth (PTG), and physical and mental health among a sample of Mississippi university students soon after Hurricane Katrina hit the Gulf coast in 2005. Resource loss was negatively associated with health, but positively associated with PTG. Religious comfort was associated with positive outcomes, and religious strain was associated with negative outcomes. Religious comfort buffered the negative effects of resource loss on emotional health. Ancillary analyses indicated that associations between resource loss and health were mediated by religious strain. Implications of this research are described for mental health practitioners engaged in disaster recovery work.